Response of Rapeseed (Brassica napus L.) and Phosphorus Fractionation in an Alkaline Soil Amended with Rock Phosphate and Elemental Sulphur - L. Habib; G.A. Alloush, R. Nasser (Journal of the Indian Society of Soil Science, 2018)
A field experiment was conducted to investigate the response of rapeseed (Brassica napus L.) to application of Syrian rock phosphate (RP) mixed with three rates of elemental sulphur (10, 20 and 50% S) in an alkaline calcareous soil compared to triple superphosphate (TSP). The RP was applied @ 800 mg P kg-1 soil. The transformations of various pools of phosphorus (P) were also studied after the harvest of rapeseed grown for two consecutive seasons. The P fractionation scheme divided calcium phosphate into three types namely, dicalcium phosphates (Ca2-P), octacalcium phosphates (Ca8-P) and apatite (Ca10-P). The results showed that rapeseed plant utilized P from Syrian RP as good as that of TSP in both seasons. Mixing of elemental S with RP showed no effects on dry matter yield in first season, whereas in the second season, all mixing rates of S increased dry matter production significantly. Mixing of RP with S influenced RP dissolution, thereby all inorganic P (Pi) fractions increased. The dominant P fractions in RP and RP+S treatments were Ca10-P, followed by Ca8-P. The opposite was true for TSP treatment. The Ca2-P was the main source of available soil P as it correlates significantly with Olsen-P.